EVALUASI INVESTASI TEKNOLOGI INFORMASI DENGAN MENGGUNAKAN DOMAIN VALUE GOVERNANCE VAL IT FRAMEWORK 2.0 (STUDI KASUS: CV.BERKA) - Ferdy Firmansyah; Wing Wahyu Winarno; Asro Nasiri (Universitas Janabadra, 2019)
In this study a study was conducted on the use of the Val IT framework in measuring the value of information technology investments. This research was conducted with a case study at CV. Berka who is engaged in public works which deals with the construction of houses. The concept of Val IT Framework 2.0, which was initiated by the Information Technology Governance Institute (ITGI) (2008), through the experience of a set team of practitioners, academics, and practices, some of the methodologies, and research to develop the Val IT framework. Development of the Val IT framework with several research activities, publications and support services. Val IT consists of a set of basic principles and the three main processes for measuring the value of IT Value Gavenance, Portfolio Managament, Investment Management.Masing these 3 main process then broken down into several sub-items. Through the business case method can provide a complete picture and transparent to the management on the benefits of an investment and helps the management to make decisions on investment, so it can be used as controls achieving the expected value of an investment in Information Technology Keywords: Val IT, Investment Technology, Value Governance